Groot. #1 - Loveness, Jeff (Guardians of the galaxy (Series), 2018)
Groot and Rocket Raccoon's road trip across the galaxy to Earth gets off to a bad start as their vehicle breaks down and, after a series of hitchhiking mishaps, the two get separated.